2017
DOI: 10.31018/jans.v9i3.1390
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability, gene action and heritability analysis for early blight resistance, yield and quality traits in tomato (Solanum lycopersicum L.)

Abstract: Nine tomato genotypes were crossed in Line ×Tester fashion to develop 18 hybrids, which, along with their parents and checks were evaluated for early blight resistance, fruit yield and quality of tomato (Solanum lyco-persicum) to know extent of combining ability for the same. IIHR1816 was found to be the best general combiner with significant highest GCA (General Combining Ability) in desirable direction for per cent disease index (-15.71), carotenoids (3.46), lycopene (2.43) and yield (13.13); while, for plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This means that the genes action of additive and nonadditive are involved in controlling the four traits. Bharathkumar et al (2017) reported the same result, stating that additive and non-additive gene action was involved in trait inheritance of days to 50% flowering, fruit firmness, and yield per hectare. Dharva et al (2018) described the same result for the number of locules per fruit.…”
Section: Additive Gene Action Mainly Controls the Fruit Shelf-life And Agronomic Traitsmentioning
confidence: 71%
“…This means that the genes action of additive and nonadditive are involved in controlling the four traits. Bharathkumar et al (2017) reported the same result, stating that additive and non-additive gene action was involved in trait inheritance of days to 50% flowering, fruit firmness, and yield per hectare. Dharva et al (2018) described the same result for the number of locules per fruit.…”
Section: Additive Gene Action Mainly Controls the Fruit Shelf-life And Agronomic Traitsmentioning
confidence: 71%